Quantification of horizontal force for the EXER-GENIE® resisted sprint training device - Ghigiarelli, Jamie J.; Ferrara, Keith J.; Yang, Yang; Abrechsten, James D.; Barat, Veronica M.; Sell, Katie M.; Gonzalez, Adam M. (Frontiers in Sports and Active Living, 2023)
Sport performance coaches use a range of modalities to apply a horizontal force (Fh) to athletes during resisted sprint training (RST). These modalities include parachutes, weighted vests, pulley devices, motored tethered devices, and, most notably, weighted sleds. Despite the widespread use of these devices, the resistance forces of the pulley devices have not been evaluated for reliability and accuracy. Therefore, the primary aim of this study was to quantify Fh of a commercially available pulley device (EXER-GENIE®) and determine how resistance force was related to the load settings on the device. A secondary aim was to identify differences in Fh between three EXER-GENIE® devices that use a 36-meter (m) rope and a 60 m rope. Using a motorized winch, a lead acid battery, and an S-beam load cell, the Fh in newtons (N) of three EXER-GENIE® devices were analyzed. Four, 10-second winch-driven trials were performed at 15 different EXER-GENIE® loads, ranging from 0.028 to 3.628 kilograms (kg), using two different 36 m devices and one 60 m device. The mean ± standard deviation for Fh was reported across the four trials for each load setting. All devices attained similar Fh across the lighter load settings (loads ≤ 0.141 kg). However, at heavier loads (loads ≥ 0.226 kg) the 60 m device had Fh values that were 50 to 85 N greater than the 36 m device. The coefficient of variation across the four trials was extremely high at light loads, but sharply decreased to <10% at heavy loads. Absolute reliability was high for each device (intraclass correlation coefficient [ICC] = 0.99). Regression analysis for Fh and EXER-GENIE® load indicated a strong positive relationship between load and Fh across all devices (R 2 = 0.96-0.99). Caution should be taken when using identical loads on the different-length pulley devices, as the 60 m device produced greater Fh than did the 36 m devices at load settings higher than 0.226 kg. These results can be used to provide coaches and practitioners with a better understanding of the magnitude of resistance that is applied when prescribing EXER-GENIE® devices for higher training loads.